Analisa Penggunaan terhadap User Interface Website Universitas Sahid Surakarta dengan Metode Heuristic Evaluation - David Pizarro (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
The Sahid Surakarta University website serves as a platform for information and academic services utilized by students, faculty, prospective students, alumni, and the general public. Consequently, the website's usability quality requires evaluation to ensure users can access information easily and comfortably. This study aims to evaluate the usability level of the Universitas Sahid Surakarta website using the Heuristic Evaluation method. A quantitative approach was employed, with data collected through observation, literature review, and questionnaires distributed to 60 Universitas Sahid Surakarta students who had previously accessed the site. Data analysis was conducted using IBM SPSS Statistics, involving validity testing, reliability testing, and descriptive analysis. The results indicate that all questionnaire items were valid, with calculated r-values exceeding the critical r-table value (0.254), and the instrument demonstrated reliability with a Cronbach's Alpha value of 0.920. The evaluation reveals that the Universitas Sahid Surakarta website possesses a good level of usability. However, certain aspects require improvement, specifically the communication of system status to users through clearer feedback during interactions. These findings are intended to assist website administrators in enhancing interface quality and ease of use, thereby delivering a superior user experience.